The centralised multi-alarm and remote monitoring using two wires system / Ahmad Maliki Omar, Ishak Ismail and Hamdani Abu Hassan - Omar, Ahmad Maliki; Ismail, Ishak; Abu Hassan, Hamdani (2003)
A reliable and effective alarm system is vital to save human lives and their properties in case of emergencies. It is no doubt that all buildings are equipped with alarm system. However, without proper co-ordination, the system does not function effectively. Although the latest technology on alarm system addresses this issue, the implementation is very costly and unaffordable to the small and medium scale customers. The main objective of this research work is to design, develop, construct and test a prototype centralised multi-alarm system which utilises and enhances the present conventional alarm system. The design also integrates the capability of remote monitoring and control of electrical loads. The system uses two wires for communication between the remote site and the central station. Maximum number of sites is 512 with maximum distance of 1.5 Km. The central station is easily relocated to any sites with less cabling work involved and minimum of two wires required. Any activated alarms or sensors will send appropriate signals directly to the central station. The developed Graphical User Interface at the central station enables the users to be alerted and informed immediately once the alarm is activated, so that immediate action can be taken.